2008
DOI: 10.1111/j.1708-8240.2008.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of A Sealant to Contaminated‐Enamel Surface: Influence of Erbium : Yttrium–Aluminum–Garnet Laser Pretreatment

Abstract: Under the conditions of this study, the conventional etching protocol (phosphoric acid without salivary contamination) is still preferable to laser-conditioning enamel surface prior to sealant application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
0
13
0
4
Order By: Relevance
“…In all these studies, it was concluded that conventional acid etching remains the most effective and simplest technique in sealants' success. Furthermore, Manhart and others 28 and Lepri and others 27 reported that if Er:YAG laser conditioning was followed by acid etching, the retention of the sealants was equal to that achieved with acid etching alone. Similarly, Sungurtekin and Oztas 29 reported that the micro- TL 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) leakage values in their laser plus acid etching group were similar to those of their acid-etching group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In all these studies, it was concluded that conventional acid etching remains the most effective and simplest technique in sealants' success. Furthermore, Manhart and others 28 and Lepri and others 27 reported that if Er:YAG laser conditioning was followed by acid etching, the retention of the sealants was equal to that achieved with acid etching alone. Similarly, Sungurtekin and Oztas 29 reported that the micro- TL 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) 0 (0%) leakage values in their laser plus acid etching group were similar to those of their acid-etching group.…”
Section: Discussionmentioning
confidence: 97%
“…While some authors [24][25][26] have reported that acid and laser etching cause similar results in terms of marginal adaptation and microleakage, some of them recommended the use of acid after laser application and also stated that the laser etching did not eliminate the need for acid etching. [27][28][29] Therefore, the search continues for the most effective enamel surface preparation to enhance sealant integrity and retention.…”
Section: Introductionmentioning
confidence: 99%
“…29 In recent years, it seems logical to investigate the effect of laser irradiation on metal surfaces of dental prosthetics to modify surface morphology even if today study results are still controversial. 14,20,[30][31][32][33] Lin et al 14 investigate whether or not erbium: yttriumaluminum-garnet (Er:YAG) lasers could improve the bonding property of zirconia ceramics to resin cement. They found that in their experimental settings, Er:YAG laser treatment cannot improve the bonding property of zirconia ceramics to resin cement, although air abrasion with alumina particles induced the highest surface roughness and SBS.…”
Section: Discussionmentioning
confidence: 99%
“…29 Thus, laser application does not eliminate the need for enamel acid etching. 30 On the other hand, some researchers reported that application of laser in conjunction with acid etching resulted in microleakage in 80% of specimens due to the formation of enamel cracks and debris at the sealant-enamel interface. They have recommended the use of argon laser for curing of the sealant material at the enamel-sealant interface to possibly increase enamel resistance to acids.…”
Section: Hard Tissue Applications Of Lasermentioning
confidence: 99%